PENGEMBANGAN MEDIA GAMBAR MENGGUNAKAN APLIKASI MOVIE MAKER PADA MATERI KLASIFIKASI MAKHLUK HIDUP UNTUK KELAS VII SMP - Dewi, Syafrina - (STKIP PGRI Sumbar, 2014)
Education is done to make human resource who has good quality and useful. The education process which is organized well is a hope to make student understand the material concept better, including biology especially living creature classification material. Because of that, teacher need to make the condition which can help student in understanding material concept of lesson well. The purpose of this research is to produced picture media by using movie maker application in living creature classification material validity and practice. This research is developing research which is used 3 steps of 4-D model (define, design, and develop). The subjects of this research 4 were validator (2 biology lectures and 2 biology teacher), and also 20 students of SMP 14 Padang. The data research is premier data which is gotten from validity and practicality questionnaire. The data which is gotten from analysis by qualitative descriptive technique. From the research is produced product like picture media which is use movie maker application with validity value 91,58% which is mean that very valid by validator, whether in content, construction, and language. The picture media movie maker which is produced has practicality value 91,25% by the teacher and 94,93% by student, that means that picture media movie maker is stated as very practice, from student interest, use process, time and activation of student. From that result can be concluded that picture media which is use movie maker application which is produced has been valid and very practice.